2019 Picture Coding Symposium (PCS) 2019
DOI: 10.1109/pcs48520.2019.8954543
|View full text |Cite
|
Sign up to set email alerts
|

Bypassing Depth Maps Transmission For Immersive Video Coding

Abstract: This paper addresses several downsides of the system under development in MPEG-I for coding and transmission of immersive media. We present a solution, which enables Depth-Image-Based Rendering for immersive video applications, while lifting the requirement of transmitting depth information. Instead, we estimate the depth information on the client-side from the transmitted views. The approach leads to an impressive rate saving (37.3% in average). Preserving perceptual quality in terms of MS-SSIM of synthesized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 11 publications
1
15
0
Order By: Relevance
“…The depth maps are not transmitted, the depth estimator is moved to the decoder side and depth maps D + are estimated from decoded textures T * to synthesize S DSDE . A first analysis of this system compared to ESDE is presented in [7] for full views and in [16] for patch atlases. In contrast to ESDE, little investigation [17] and improvement have been done towards the DSDE system up to this date.…”
Section: A Systems For Immersive Video Codingmentioning
confidence: 99%
See 2 more Smart Citations
“…The depth maps are not transmitted, the depth estimator is moved to the decoder side and depth maps D + are estimated from decoded textures T * to synthesize S DSDE . A first analysis of this system compared to ESDE is presented in [7] for full views and in [16] for patch atlases. In contrast to ESDE, little investigation [17] and improvement have been done towards the DSDE system up to this date.…”
Section: A Systems For Immersive Video Codingmentioning
confidence: 99%
“…We have shown in our previous work, that most of the downsides of ESDE are solved by completely bypassing the transmission of depth maps and then performing the depth estimation at the decoder side using the decompressed texture views. This approach is called decoder side depth estimation (DSDE) [7]. In particular, this approach enables a significant improvement in coding efficiency because most of the geometry can be estimated from the decoded textures at the decoder.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, because the proposal does not utilize any color information, its usability is very high for decoder-side depth estimation [46]. The quality of depth maps estimated using encoded input views can vary significantly, depending on the available bitrate [47].…”
Section: Figure 2 Inter-view Redundancy Removal Using Miv: Input VImentioning
confidence: 99%
“…This approach is based on reducing the depth map transmission from the encoder side, and on moving a part of the depth estimation process to the decoder side. Recently, it has been shown that decoderside depth estimation (DSDE) can efficiently recover the depth maps at the decoder side while reducing the pixel rate by 50% and saving 37.3% in terms of Bjøntegaard delta (BD) rate metric [10], when applied to the aforementioned MV-HEVC + VVS framework [11], [2]. Hence, the DSDE approach was studied in the case of full views, where the depth estimation process took advantage of many views that are available at the decoder.…”
Section: Introductionmentioning
confidence: 99%